Chinese executive compensation: the role of asymmetric performance benchmarks. Issue 4 (2nd May 2016) - Cordeiro, James; He, Lerong; Conyon, Martin; Shaw, Tara
Abstract : We study asymmetric performance benchmarking in Chinese executive compensation contracts between 2000 and 2010. We predict that while relative performance evaluation criteria are important in executive pay contracts, managerial power and influence will result in a decoupling between pay and performance. We predict that Chinese managers are rewarded for superior performance but not penalized for inferior performance. We test this asymmetric pay-for-performance hypothesis using three performance benchmarks: whether firm performance is positive/negative, above/below industry average, and above/below regional average. We find the sensitivity between executive compensation and firm accounting performance is asymmetric. It is significantly stronger when firm accounting performance is positive or firm performance exceeds industry or regional median benchmarks compared to cases when firm accounting performance is negative or is below industry or regional median benchmarks. We find little evidence that ownership structure and internal governance mechanisms moderate the asymmetric pay-for-performance relationship.